2013
DOI: 10.1186/1471-2474-14-191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cord pretension and stiffness of the Dynesys system spacer on the biomechanics of spinal decompression- a finite element study

Abstract: BackgroundThe Dynesys system provides stability for destabilized spines while preserving segmental motion. However, clinical studies have demonstrated that the Dynesys system does not prevent adjacent segment disease. Moreover, biomechanical studies have revealed that the stiffness of the Dynesys system is comparable to rigid fixation. Our previous studies showed that adjusting the cord pretension of the Dynesys system alleviates stress on the adjacent level during flexion. We also demonstrated that altering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
4
11
0
Order By: Relevance
“…That disc stress increases more extensively in flexion than in other moments suggests that discs sustain more stress during flexion. The maximum annulus stress occurring at the anterior edge of the annulus fibrosus during flexion, as shown in Figure 2 , corresponds to that reported in a previous study [ 18 ], which also demonstrated that the greatest annulus stress occurred at the adjacent cranial level located at the anterior edge of the annulus fibrosus. The disc stress distribution shown in Figure 2 reveals that AWE showed a smaller increase in stress at the adjacent level than did FUS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…That disc stress increases more extensively in flexion than in other moments suggests that discs sustain more stress during flexion. The maximum annulus stress occurring at the anterior edge of the annulus fibrosus during flexion, as shown in Figure 2 , corresponds to that reported in a previous study [ 18 ], which also demonstrated that the greatest annulus stress occurred at the adjacent cranial level located at the anterior edge of the annulus fibrosus. The disc stress distribution shown in Figure 2 reveals that AWE showed a smaller increase in stress at the adjacent level than did FUS.…”
Section: Discussionsupporting
confidence: 88%
“…The annulus ground substance was modeled based on an incompressible, hyperelastic, 2-parameter (C1, C2) Mooney-Rivlin formulation, and the nucleus pulposus was modeled as an incompressible fluid. Model construction and validation have been well documented in previous studies [ 17 , 18 ].
Figure 1 Spine and implant FE models used in this study.
…”
Section: Methodsmentioning
confidence: 99%
“…The annulus material was modeled based on a hyperelastic, incompressible, 2parameter (C1, C2) Mooney-Rivlin formulation, and the nucleus pulposus was established as an incompressible fluid. Convergence testing and validation of the intact model were completed in previous studies [18,19], with the results being similar to other published finite element models [20]. The study of Dreischarf et al [20] also revealed that our finite element models can be used as an improved predictive tool in order to estimate the response of the lumbar spine using different motion input for various cases analyzed.…”
Section: Methodssupporting
confidence: 71%
“…Previous studies by the authors developed a finite element model of an intact lumbar spine in ANSYS 14.0 (ANSYS Inc., Canonsburg, PA, USA) [17][18][19], including osseoligamentous L1-L5 vertebrae, endplates, intervertebral discs, posterior bony elements, and all 7 ligaments (Fig. 1a).…”
Section: Methodsmentioning
confidence: 99%
“…1). The novel implant for the Dynesys + Fusion (DTO) model consisted of six titanium alloy screws (diameter: 6.4 mm, length: 45 mm) and using PEEK or OstaPek rod instead of Titanium Ti rod Moreover, two PCU spacers (Diameter: 12 mm, Length: 30 mm) and 300 N pretention PET cord, which contacted the screw in Dynesys model [16]. The intact model was modified to simulate the instability caused by a discectomy, which modeled by removing some part of the annulus from the anterior side of the disc [17] that produces natural physiological spinal motions (Fig.…”
Section: Methodsmentioning
confidence: 99%